PENGARUH LATIHAN PRO AGILITY SHUTTLE TERHADAP KELINCAHAN PEMAIN SEPAKBOLA SMA PGRI PEKANBARU - Yelzi Riswindra Riswindra; Ramadi '; Ardiah Juita Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT : This study was conducted to determine whether there was an effect of exercise Pro Agility Agility Shuttle to the high school football players PGRI Pekanbaru, so that when the sprint after the ball first player to get the ball from the opponent.The shape of this research is the experimental treatment (Experimental), the population in this study was a high school football pemaian PGRI pekanbaru, the sample in this study is the high school students PGRI active in training, amounting to 16 players. The sampling technique that is non-random sampling (non-random). Non-random sampling is a sampling process that is not based on randomization. In this study researchers used a purposive sampling technique. Purposive sampling is a sampling of the researcher pointed directly who will be sampled in the study, but the selection based on the specific objectives of the research conducted. Researchers consider the suitability of a problem with the selected individuals.The instruments used in this research is the Illinois Agility Run Test, which aims to measure the agility of movement. After that, the data is processed with statistics, to test the normality of the test at a significant level 0,05α lilifors. The hypothesis is the effect of exercise Pro Agility Shuttle Against Agility.Based on t test analysis produces Thitung of 9.6 and Ttabel1,753, means Thitung> Ttabel. Based on the analysis of statistical data, there are an average of 18.30 and Pree-test average post-test at 17:40, then the data is normal. Thus, there is the effect of exercise Pro Agility Agility Shuttle to the high school football players PGRI pekanbaru. Keywords: Pro Agility Shuttle, Agility